Detection and typing of herpes simplex viruses by using recombinant immunoglobulin fragments produced in bacteria. - Cattani, P (1997)
Thirty-seven bacterial clones producing human recombinant monoclonal antibody Fab fragments (rFabs) reactive to herpes simplex virus (HSV) antigens were selected from a human combinatorial antibody library constructed in a phage-display vector by a panning procedure against an HSV lysate. Thirty-four of the HSV-specific rFabs were able to specifically recognize HSV-infected cells in indirect immunofluorescence (IF) assays; of these, 25 recognized cells infected by either HSV type 1 (HSV-1) or HSV-2, while 9 recognized only HSV-1-infected cells. One HSV type-common rFab (rFab H37) and one HSV-1-specific rFab (rFab H85) were further evaluated as reagents for viral detection and typing by IF staining in 134 HSV-positive (72 HSV-1 and 62 HSV-2) viral cultures from clinical specimens. The results obtained with these two rFabs were fully consistent with those obtained with a commercial preparation of fluorescein-labeled anti-HSV type-specific murine monoclonal antibodies. The detection sensitivity with the type-common rFab in indirect IF assays was higher overall than that provided by the type-specific murine monoclonal antibodies. Preparations of rFabs suitable for IF staining can be easily and inexpensively obtained in a clinical microbiology laboratory from Escherichia coli cultures. Similar HSV-specific rFabs, therefore, could be advantageous for in vitro diagnostic purposes.